Morphosyntactic Cues for Quantifier Comprehension in Children. Issue 4 (1st October 2020) - Shetreet, Einat; Novogrodsky, Rama
ABSTRACT: Universal quantifiers, which refer to groups of individuals or events, can express a subtle distinction between collective (unified or simultaneous) and distributive (individuated and separate) events. Indeed, English uses different quantifiers for this distinction ("all" and "each", respectively). Hebrew, however, has a single universal quantifier. Thus, the collective/distributive distinction associated with the universal quantifier is represented morphosyntactically. This study examined whether Hebrew-speaking children (4–6 year olds) detect the collective/distributive distinction based on morphosyntactic cues alone and whether they show similar performance pattern as adults. Using a novel drawing task, instructions were given in either a collective-preferred form or a distributive form, asking participants to add drawings to pictures of multiple items. Within-subjects (Experiment 1) and between-subjects designs (Experiment 2) were used. Overall, children distinguished between the forms, indicating that they attended the specific morphosyntic cues of these two forms. They produced distributive drawings following the distributive form, similarly to adults. However, they alternated between distributive and collective drawings following the collective-preferred form, unlike adults who mostly gave collective responses. We discuss a possibility for the interplay between the meaning of the universal quantifier and the morphosyntactic cues in children's performance. This study provides insights into the acquisition of meaning that depends on morphosyntax.